2013
DOI: 10.1007/s40520-013-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of use and presenting complaints of older patients visiting an Emergency Department in Italy

Abstract: Older adults use the ED appropriately also in Italy. Trauma with complications (fracture) and various presenting complaints underlying medical problems accounted for more than 50 % of ED visits and hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
6
20
2
1
Order By: Relevance
“…Furthermore, in Singapore, a study conducted by Foo et al 19 reported that falls were the most common complaint among elderly patients, which increased their odds of getting admitted compared to the control group (OR: 1.9; 95% CI: 1.4–2.6), and a similar report from the Italy revealed that older trauma patients have high odds (OR: 5.12, 95% CI: 3.34–7.85) 20 . In the present study, the most common diseases and complaints in elderly patients were URTI (17.5%, CI: 17.1–17.9), chest pain (14.5%, 95% CI: 14.2–14.9), injury (11.7%, 95% CI: 11.4–12.1), myalgia (8.9%, 95% CI: 8.6–9.2), and LRTI (7.1%, 95% CI: 6.8–7.4).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, in Singapore, a study conducted by Foo et al 19 reported that falls were the most common complaint among elderly patients, which increased their odds of getting admitted compared to the control group (OR: 1.9; 95% CI: 1.4–2.6), and a similar report from the Italy revealed that older trauma patients have high odds (OR: 5.12, 95% CI: 3.34–7.85) 20 . In the present study, the most common diseases and complaints in elderly patients were URTI (17.5%, CI: 17.1–17.9), chest pain (14.5%, 95% CI: 14.2–14.9), injury (11.7%, 95% CI: 11.4–12.1), myalgia (8.9%, 95% CI: 8.6–9.2), and LRTI (7.1%, 95% CI: 6.8–7.4).…”
Section: Discussionmentioning
confidence: 89%
“…A study by Yim et al 24 found that the total proportion of non-urgent visits in three Hong Kong EDs was less than 5%. Another study by Salvi et al 20 on older patients visiting the ED in Italy reported that the proportion of non-urgent visits was 3%. However, the present study found this rate to be much higher (23.4%).…”
Section: Discussionmentioning
confidence: 97%
“…27 Even in countries with greater healthcare utilization amongst men, there is a marked female predominance in the oldest ED patients. 28,29,30 In this study there were more women in all age-groups, with the exception of young-older adults. There was an increased chance of admission for men in all age categories, except in the old-older group, where the probability of admission was similar to women.…”
Section: Discussionmentioning
confidence: 49%
“…Their top diagnoses were "symptoms, signs, and ill-defined conditions" (25%) and "injury and poisoning" (17%). Salvi et al [15] also reported their findings in Italy that dyspnea and abdominal pain were the most frequent nontrauma presenting complains among geriatric patients and represented the main causes for admission. These are similar to our fi ndings.…”
Section: Discussionmentioning
confidence: 88%